Optimization of the surface plasmon resonance minimum detection algorithm for improvement of method sensitivity - Khrystosenko, R.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Developed in this work is the information technology for improvement of the sensitivity inherent to the surface plasmon resonance (SPR) method by optimization of the resonance curve minimum detection algorithm. Simulation of SPR sensor response has been performed using the Fresnel equations with account of noise contribution and the Jones calculus. It has been demonstrated that using third-order polynomial approximation in the angular scanning range of θSPR ± 0.5° with 100 experimental points improves the sensitivity of “Plasmon” series instruments by an order of magnitude.